2018
DOI: 10.1007/s13596-018-0315-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidative, antimicrobial and anti-cancer activities of Asteriscus graveolens (Forssk) essential oil

Abstract: This work is devoted to the study of the chemical composition and the evaluation of the biological activities of essential oils (EOs) extracted from the flowers of Asteriscus graveolens Forssk. plant. The EO sample was obtained by hydrodistillation and the chemical composition analysis was performed using GC and GC/MS. The major chemical components characterizing the EO were cis-chrysanthenyl acetate (44.30%) and cis-8-acetoxychrysanthenyl acetate (33.70%). Antioxidant activity was determined using DPPH and Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The total antioxidant capacity (TAC) determined by ammonium molybdate method revealed that the antioxidant capacity of EOAG was on the order of 1048.38 ± 10.23 µg EAA/mg, while BHT and quercetin, which were used as chemical references recorded 987.46 ± 7.47 µg EAA/mg and 891.73 ± 8.22 µg/mg, respectively ( Figure 4 ). These results are in accordance with those reported by Aouissi and co-authors, who determined the total antioxidant capacity of EOs of A. graveolens from Algeria was 0.28 AAEC/mg [ 18 ]. Previous literature reported that terpenic compounds, i.e., carvacrol and α-thujone, decreased the degree of peroxidation of the phospholipids present in liposomes in the presence of iron (III), which might explain the antioxidant power of EOAG in this study [ 32 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The total antioxidant capacity (TAC) determined by ammonium molybdate method revealed that the antioxidant capacity of EOAG was on the order of 1048.38 ± 10.23 µg EAA/mg, while BHT and quercetin, which were used as chemical references recorded 987.46 ± 7.47 µg EAA/mg and 891.73 ± 8.22 µg/mg, respectively ( Figure 4 ). These results are in accordance with those reported by Aouissi and co-authors, who determined the total antioxidant capacity of EOs of A. graveolens from Algeria was 0.28 AAEC/mg [ 18 ]. Previous literature reported that terpenic compounds, i.e., carvacrol and α-thujone, decreased the degree of peroxidation of the phospholipids present in liposomes in the presence of iron (III), which might explain the antioxidant power of EOAG in this study [ 32 ].…”
Section: Resultssupporting
confidence: 92%
“…The antioxidant power of EOAG remains important when compared to that investigated by Alilou and co-authors [ 25 ], reporting an IC 50 value of A. graveolens on the order of 249 µg/mL. The antioxidant potency of EOAG, as assessed by the DPPH assay, with an IC 50 value of 34.81 ± 1.12 µg/mL is better than that found by Aouissi and co-authors who reported that the IC 50 value of A. graveolens indigenous to Algeria was 420.16 mg/mL [ 18 ]. This difference can be due to differences in environmental and edaphic influences the plant growth, resulting in phytochemical composition changes, which in turn affect antioxidant power [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oils of Bubonium graveolens contain mainly oxygenated monoterpenes (37.6% in leaves, and 60.3% in flowers), with 1,8-cinoeole (21.5%) as the main constituent in the flowers 1 . The other major components are cis-chrysanthenyl acetate (44.30%), cis-8-acetoxychrysanthenyl acetate (33.70%), and τ-muurolol (6.51%) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study was carried out by Znini et al on the effect of EO from A. graveolens leaves on corrosion inhibition 13 . For the last three articles, studies have been carried out on the antioxidant activity and hemolytic effect of the plant extracts 14 , the antioxidant, antibacterial, antifungal and anticancer activity of EO 15 and finally a final study that confirms the antioxidant and antibacterial power of the plant 16 . On the other hand, we have not found any literature dealing with the analgesic activity of this plant, which is why we have taken the initiative to test these essential oils to evaluate central and peripheral analgesia in an animal model.…”
Section: Introductionmentioning
confidence: 99%